Accuracy study on “Osteorisk”: a new osteoporosis screening clinical tool for women over 50 years old - Steiner, Marcelo Luis; Fernandes, César Eduardo; Strufaldi, Rodolfo; Azevedo, Lucia Helena de; Stephan, Cristina; Pompei, Luciano Melo; Peixoto, Sérgio (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Osteoporosis is the greatest cause of quality-of-life reductions, morbidity and mortality among postmenopausal women, with growing incidence as populations age. Clinical tools like Osteorisk provide an easyaccess and low-cost alternative method that helps physicians to reduce the need for dual-energy X-ray absorptiometry (DXA), the expensive gold standard examination for diagnosing osteoporosis. The aim here was to study the accuracy of Osteorisk using heel ultrasonography for bone mineral density (BMD). DESIGN AND SETTING: Cross-sectional study, at Faculdade de Medicina do ABC. METHODS: A structured questionnaire was applied to 615 postmenopausal women, with anthropometric measurements, Osteorisk calculations and quantitative ultrasound on the heel using Sonost 2000 equipment. RESULTS: 461 women were included, with mean age 60 ± 9 years, weight 67.6 ± 12.9 kg and body mass index (BMI) 28.8 ± 5.0 kg/m2. Their Osteorisk classifications were: 61.0% lowrisk, 28.4% medium-risk and 10.6% high-risk. Quantitative ultrasound showed 81.3% low-risk, 10.0% medium-risk and 8.7% high-risk regarding osteoporosis. Statistically significant results were observed (p < 0.001) when Osteorisk was correlated with age, years since menopause and BMI. Correlating these same variables with quantitative ultrasound, statistically significant results were observed for age (p < 0.001), years since menopause (p < 0.001) and BMI (p < 0.006). The sensitivity, specificity, negative predictive value and positive predictive value for Osteorisk were 64%, 6.7%, 89% and 30.6%, respectively. CONCLUSION: Osteorisk is a valid tool for screening for women at low risk of osteoporosis, making it possible for these women not to have to undergo densitometry.